Особливості поглинання та випромінювання світла вільними електронами в феромагнітних напівпровідниках - Semchuk, O. Yu. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2016)
General expressions are got for an asorptance, and at presence of hot electrons, and for intensity of scattering light by free electrons in ferromagnetic semiconductors (FMSC) for a case, when dominant is electron-magnon interaction, in that dependence is taken into account on the concentration of electrons, their temperature and magnon temperature. The classic and quantum cases are considered. It is shown that in the classic range of frequencies, if there is not a warming-up of electrons and magnon, an asorptance by the free electrons of light in FMSC only on a multiplier differs from the classic formula of Dryde. It is set that intensity of spontaneous radiation of hot electrons in FMSC does not depend on frequency of light in the classic range of frequencies and exponentially falls in the quantum area of frequencies.